2015
DOI: 10.1186/s13287-015-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of murine induced pluripotent stem cell-derived cardiomyocytes to hypoxia and nutrient deprivation

Abstract: IntroductionInduced pluripotent stem cell-derived cardiomyocytes (iPS-CMs) may be suitable for myocardial repair. While their functional and structural properties have been extensively investigated, their response to ischemia-like conditions has not yet been clearly defined.MethodsiPS-CMs were differentiated and enriched from murine induced pluripotent stem cells expressing enhanced green fluorescent protein (eGFP) and puromycin resistance genes under the control of an α-myosin heavy chain (α-MHC) promoter. iP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…Thus, assays of cell viability are often performed to assess the role of a particular genetic or pharmacological intervention in exacerbating or protecting the cell from H/R-induced cell death. Viability may be measured with a variety of assays, including lactate dehydrogenase (LDH) release or propidium iodide exclusion as an indicator of membrane integrity ( 24 , 31 , 58 ). Apoptosis is assessed with TUNEL or annexin V staining ( 24 , 58 , 166 ).…”
Section: In Vitro and Ex Vivo Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, assays of cell viability are often performed to assess the role of a particular genetic or pharmacological intervention in exacerbating or protecting the cell from H/R-induced cell death. Viability may be measured with a variety of assays, including lactate dehydrogenase (LDH) release or propidium iodide exclusion as an indicator of membrane integrity ( 24 , 31 , 58 ). Apoptosis is assessed with TUNEL or annexin V staining ( 24 , 58 , 166 ).…”
Section: In Vitro and Ex Vivo Modelsmentioning
confidence: 99%
“…Viability may be measured with a variety of assays, including lactate dehydrogenase (LDH) release or propidium iodide exclusion as an indicator of membrane integrity ( 24 , 31 , 58 ). Apoptosis is assessed with TUNEL or annexin V staining ( 24 , 58 , 166 ). Mitochondrial damage, including disruption of mitochondrial membrane potential, is also a key component of cellular injury after H/R and may be assessed using fluorescent dyes, such as tetramethylrhodamine methyl ester (TMRM).…”
Section: In Vitro and Ex Vivo Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For treatment with 2-methoxyestradiol (2ME; Sigma-Aldrich, St. Louis, MO), an inhibitor of HIF-1α accumulation [ 29 , 30 ], cells were cultured in fully supplemented M199 containing 3 μM 2ME under normoxic (21% O 2 ) or hypoxic (1%) conditions for 24 hours. The 1% O 2 (~7 mmHg) is commonly used to induce hypoxic treatment on tissue or cells [ 8 , 54 , 57 , 58 ]. Our previous studies showed that 1% O 2 induced cellular and molecular responses in cardiomyocytes such as the nuclear accumulation of HIF-1α [ 8 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Combining cell and gene therapy offers the advantage that cells can be genetically engineered ex vivo prior to transplantation, offering a safer alternative and more precise control of gene expression compared to gene therapy alone. 27,38,[45][46][47] Another such approach involves the ex vivo engineering of cell grafts with mixtures of physiologically relevant cell types, such as cardiomyocytes; cardiac precursors; and vascular, neuronal, immune, and mesenchymal cell types, 35,41,[48][49][50][51][52][53][54] which may offer a more comprehensive regenerative strategy compared to each cell type alone, given that both cardiomyogenic and non-cardiomyogenic cells are necessary for heart function and regeneration.…”
mentioning
confidence: 99%